Дослідження параметрів диспергування мікроемульсій - Самойчук, Кирило Олегович; Samoichuk, Kyryl; Кюрчев, Сергій Володимирович; Kiurchev, Serhii; Паляничка, Надія Олександрівна; Palianychka, Nadiia; Ковальов, Олександр Олександрович; Kovalov, Oleksandr (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: У роботі наведено методику розрахунку дисперсності емульсій, що ґрунтується на визначенні критерію Вебера для диспергаторів-гомогенізаторів жирових емульсій, які застосовуються в сільському господарстві, переробній та харчовій промисловості. Подано стислий аналіз існуючих пристроїв для диспергування та гомогенізації емульсій. Описано експериментальні дані з візуального спостереження процесу руйнування дисперсних частинок жирових емульсій і крапель рідини. Охарактеризовано основні теорії та механізми диспергування, на підставі чого виділено узагальнювальний фактор процесу руйнування дисперсних частинок емульсії – швидкість потоку емульсії, яка є визначальною для критерію руйнування рідких частинок – критерію Вебера. Проаналізовано режими руйнування дисперсних частинок за Ю. Ф. Дитякіним та їх застосовність до жирових в’язких емульсій. Розраховано можливість диспергування жирових кульок молочної емульсії під дією вібраційної моди. Обґрунтовано характер руйнування частинок емульсії, що узгоджується з дослідженнями Ю. Ф. Дитякіна, теоріями гомогенізації М. Н. Орешиної, П. О. Ребіндера та Г. Віттіга, а також з візуальними спостереженнями Ф. Іннінгса. Наведено рівняння, що дозволяють розрахувати середню дисперсність емульсії, необхідну швидкість ковзання частинки, критичне значення критерію Вебера та час, потрібний для повного руйнування частинки після обробки в клапанних струминних і пульсаційних диспергаторах та гомогенізаторах для обробки жирових емульсій. Розраховано критичне значення критерію Вебера для гомогенізації молочної емульсії. Алгоритм розрахунку базується на визначенні критеріїв Вебера, Лапласа та розрахунку часу, необхідного для руйнування частинки емульсії. /// EN: This paper presents a methodology for calculating the dispersion degree of emulsions based on the determination of the Weber criterion for disperser–homogenizers of fat emulsions used in agriculture, food processing, and the food industry. The proposed approach makes it possible to evaluate the conditions of effective droplet breakup depending on hydrodynamic parameters of the flow and physicochemical properties of the dispersed system. A brief analytical review of existing devices for emulsion dispersing and homogenization is provided, including valve-type, jet, pulsation, and rotor–pulsation homogenizers. Experimental data obtained from visual observations of the deformation and breakup of dispersed particles of fat emulsions and liquid droplets are described, highlighting the characteristic stages of particle elongation and fragmentation under high shear conditions. The main theories and mechanisms of emulsion dispersing are characterized and systematized. Based on this analysis, a generalized governing factor of the destruction of dispersed emulsion particles is identified, namely the emulsion flow velocity. This parameter plays a decisive role in the particle breakup criterion expressed by the Weber number, which determines the balance between inertial forces and surface tension forces acting on liquid particles. The modes of dispersed particle breakup according to Yu. F. Dityakin are analyzed, and their applicability to viscous fat emulsions is evaluated. The possibility of dispersing fat globules of a milk emulsion under the action of a vibrational mode is theoretically assessed. The nature of emulsion particle breakup is substantiated and shown to be consistent with the experimental studies of Yu. F. Dityakin, the homogenization theories developed by M. N. Oreshina, P. O. Rebinder, and G. Wittig, as well as the visual observations reported by F. Inning. Equations are presented that allow the calculation of the average emulsion dispersion, the required particle slip velocity, the critical value of the Weber criterion, and the time necessary for complete particle breakup after treatment in valve-type jet and pulsation dispersers and homogenizers used for fat emulsions. The critical Weber number for the homogenization of milk emulsion is calculated. The calculation algorithm is based on determining the Weber and Laplace criteria, as well as calculating the time required for the breakup of an emulsion particle.
Investigation of dispersing parameters of microemulsions
Keywords: диспергування; гомогенізація; емульсія; обчислення; дисперсність; мікроемульсія; dispersing; homogenization; emulsion; calculation; dispersion; microemulsion